Panóptico da modernidade: transparência, accountability e controles sociais no Conselho Nacional do Ministério Público - Moreira, Renan Bambini (2019)
In representative democracies, the presence of instruments capable of obliging public agents to justify the fulfillment of their duties is indispensable. For this accountability to occur, the existence of transparency is fundamental. The term encompassing transparency, control and accountability is accountability, which is recurrently identified in the literature as an indicator of the democratic quality of a country. In this sense, the higher the level of transparency, the greater the accountability. Formed by a specialized bureaucracy and with powers related to the power of supervision and defense of the interests of the State, it is expected that the Public Prosecution Service (MP) has difficulties in submitting to some model of external control. The National Council of the Public Prosecution Service (CNMP) acts as this external control body, being an instrument for improving control, providing mechanisms to assist and facilitate the exercise of social control. As the formation of the Council is most of the MP itself, the strict compliance with what is defined by the current regulations and the permeability of democratic spaces for popular participation within the control body is questioned. Thus, this paper aimed to analyze how the CNMP remains permeable to society and, at the same time, submits to the accountability process. The results support the hypothesis of a bureaucratic isolation due to the poor performance in terms of transparency making the body impervious to social control, caused mainly by the bureaucratic formation of the Council with strong political ties with the executive, legislative and judiciary powers. It was demonstrated in the active transparency assessment that the CNMP meets 96.49% of the requirements on executive-budget content, by contrast, only 33.33% of the requirements for popular participation. This result reveals an institutionalized isolation absent from any social control mechanism. In the evaluation of passive transparency, 62.5% of the responses sent presented all the requested information and only 25% of the responses sent were classified as satisfactory, indicating the development of a powerful and independent bureaucracy, which puts democracy itself at risk. Considering the facts raised, it is evident that the CNMP did not show significantly positive results for transparency and accountability. Moreover, regarding the subterfuge of functional independence and discretion, the CNMP is even more insulated in the democratic context, removing any attempt. of social control.